Medical Populism and the Moral Right to Healthcare - Mabaquiao, Napoleon Jr.; Dacela, Mark Anthony (Diametros, 2023)
Medical populism, as a political style of handling the challenges of a public health crisis, has primarily been analyzed in terms of its influence on the efficacy of governmental efforts to meet the challenges of the current pandemic (such as those related to testing, vaccination, and community restrictions). As these efforts have moral consequences (they, for instance, will affect people’s wellbeing and may lead to suffering, loss of opportunities, and unfair distributions), an analysis of the ethics of medical populism is much needed. In this essay, we address the need to analyze the moral dimension of medical populism by relating it to issues in healthcare ethics. Specifically, we identify the moral significance of medical populism by demonstrating how it contributes to the failure of governments to discharge their moral duty to provide for the healthcare needs of their people, and, correlatively, to the violation of the people’s moral right to healthcare. We argue that with medical populism, governments tend to mishandle the constraints that would morally justify their shortcomings in fulfilling such duty. We identify such constraints as mainly referring to the governments’ given (economic and institutional) capacities and the relative degree of incumbency of their competing duties.